Diversity and Excellence in Higher Education
XXII, 244 p.
Keywords: "Diversity and excellence in Higher Education seem to be conflicting concepts. Nevertheless, they are dynamic and closely intertwined -- indeed they may even require each other. The book brings together insights from ten different countries to analyse these multi-facetted phenomena and discuss how they may be reconciled within higher education. To set the overall context, it critically addresses markets and managerialism, whilst foregrounding the dangers of certain behavior that European countries are currently, though often unwisely, copying from the U.S. In a mass Higher Education system, the social basis of the student body diversifies – a fact that creates new challenges for planners and managers. The authors’ study of diversity concentrates particularly upon issues of equity and justice for students, addressing their life cycle transitions from school to higher education, degree completion, postgraduate education and employability. It also considers challenges posed by diversification at the institutional level, encompassing changes in management, leadership, governance and performance assessment. It addresses attempts to achieve excellence by selectivity, thereby contributing to the stratification of university systems; and it explores attempts to achieve excellence by merging smaller institutions to form larger entities. The book’s overall conclusion is that diversity and excellence are not necessarily enemies but relatives who cannot escape the bond between them. " .